Intracellular amyloid toxicity induces oxytosis/ferroptosis regulated cell death - Huang, Ling (Cell Death Dis, 2020)
Amyloid beta (Aβ) accumulates within neurons in the brains of early stage Alzheimer’s disease (AD) patients. However, the mechanism underlying its toxicity remains unclear. Here, a triple omics approach was used to integrate transcriptomic, proteomic, and metabolomic data collected from a nerve cell model of the toxic intracellular aggregation of Aβ. It was found that intracellular Aβ induces profound changes in the omics landscape of nerve cells that are associated with a pro-inflammatory, metabolic reprogramming that predisposes cells to die via the oxytosis/ferroptosis regulated cell death pathway. Notably, the degenerative process included substantial alterations in glucose metabolism and mitochondrial bioenergetics. Our findings have implications for the understanding of the basic biology of proteotoxicity, aging, and AD as well as for the development of future therapeutic interventions designed to target the oxytosis/ferroptosis regulated cell death pathway in the AD brain.